Global variations and drivers of nitrous oxide emissions from forests and grasslands - Yu, Lijun; Zhang, Qing; Tian, Ye; Sun, Wenjuan; Scheer, Clemens; Li, Tingting; Zhang, Wen (Frontiers in Soil Science, 2022)
Nitrous oxide (N2O) emissions are highly variable due to the complex interaction of climatic and ecological factors. Here, we obtained in-situ annual N2O emission flux data from almost 180 peer-papers to evaluate the dominant drivers of N2O emissions from forests and unfertilized grasslands at a global scale. The average value of N2O emission fluxes from forest (1.389 kg Nha-1yr-1) is almost twice as large as that from grassland (0.675 kg Nha-1yr-1). Soil texture and climate are the primary drivers of global forest and grassland annual N2O emissions. However, the best predictors varied according to land use and region. Soil clay content was the best predictor for N2O emissions from forest soils, especially in moist or wet regions, while soil sand content predicted N2O emissions from dry or moist grasslands in temperate and tropical regions best. Air temperature was important for N2O emission from forest, while precipitation was more efficient in grassland. This study provides an overall understanding of the relationship between natural N2O emissions and climatic and environmental variables. Moreover, the identification of principle factors for different regions will reduce the uncertainty range of N2O flux estimates, and help to identify region specific climate change mitigation and adaptation strategies.